Impact of Biomass Burning on Arctic Aerosol Composition - Gramlich, Yvette; Siegel, Karolina; Haslett, Sophie L.; Cremer, Roxana S.; Lunder, Chris; Kommula, Snehitha M.; Buchholz, Angela; Yttri, Karl Espen; Chen, Gang; id_orcid:0 000-0002-1507-4622; Krejci, Radovan; Zieger, Paul; et al. (American Chemical Society, 2024)
Emissions from biomass burning (BB) occurring at midlatitudes can reach the Arctic, where they influence the remote aerosol population. By using measurements of levoglucosan and black carbon, we identify seven BB events reaching Svalbard in 2020. We find that most of the BB events are significantly different to the rest of the year (nonevents) for most of the chemical and physical properties. Aerosol mass and number concentrations are enhanced by up to 1 order of magnitude during the BB events. During BB events, the submicrometer aerosol bulk composition changes from an organic- and sulfate-dominated regime to a clearly organic-dominated regime. This results in a significantly lower hygroscopicity parameter κ for BB aerosol (0.4 ± 0.2) compared to nonevents (0.5 ± 0.2), calculated from the nonrefractory aerosol composition. The organic fraction in the BB aerosol showed no significant difference for the O:C ratios (0.9 ± 0.3) compared to the year (0.9 ± 0.6). Accumulation mode particles were present during all BB events, while in the summer an additional Aitken mode was observed, indicating a mixture of the advected air mass with locally produced particles. BB tracers (vanillic, homovanillic, and hydroxybenzoic acid, nitrophenol, methylnitrophenol, and nitrocatechol) were significantly higher when air mass back trajectories passed over active fire regions in Eastern Europe, indicating agricultural and wildfires as sources. Our results suggest that the impact of BB on the Arctic aerosol depends on the season in which they occur, and agricultural and wildfires from Eastern Europe have the potential to disturb the background conditions the most. ISSN:2472-3452